Net reductions or spatiotemporal displacement of intentional wildfires in response to arrests? : evidence from Spain - Butry, David T. (International journal of wildland fire, 2019)
Research to date has not examined how the impacts of arrests manifest across space and time in environmental crimes. We evaluate whether arrests reduce or merely spatiotemporally displace intentional illegal outdoor firesetting. Using municipality-level daily wildfire count data from Galicia, Spain, from 1999 to 2014, we develop daily spatiotemporal ignition count models of agricultural, non-agricultural and total intentional illegal wildfires as functions of spatiotemporally lagged arrests, the election cycle, seasonal and day indicators, meteorological factors and socioeconomic variables. We find evidence that arrests reduce future intentional illegal fires across space in subsequent time periods.This research was partly funded by Project ECO2017–89274-R MINECO/AEI/FEDER, UES